A review of the relationships of Xenochrophis cerasogaster Cantor, 1839 (Serpentes: Colubridae) to its congeners - Purkayastha, Jayaditya; Kalita, Jatin; Brahma, Rajeev Kungur; Doley, Robin; Das, Madhurima (Zootaxa, 2018)
We sampled snakes of the genus Xenochrophis from across Northeast India. The snakes were evaluated for both morphological and molecular parameters. Phylogenetic relationship was reconstructed using mitochondrial genes (Cytb, 12s rRNA, ND4). The genus Xenochrophis was found to be paraphyletic, X. piscator complex and X. punctulatus form a single clade with Atretium schistosum as their sister taxon. X. cerasogaster forms a distinct lineage. X. vittatus and X. trianguligerus are related to the genus Rhabdophis. Herein it is recommended that X. piscator complex, i.e. X. asperrimus, X. flavipunctatus, X. melanzostus, X. piscator, X. sanctijohannis, X. schnurrenbergeri and X. tytleri, as well as X. punctulatus be reallocated to the genus Fowlea